Gender stereotyping in student perceptions of teaching excellence: applying the shifting standards theory. Issue 7 (10th November 2022) - Kwok, Kathryna; Potter, Jacqueline
ABSTRACT: Existing characterisations of student conceptions of teaching excellence (TE) implicitly position it as an objective construct. This study investigated gendered differences in student-submitted nominations ( n = 418) for an excellence award in a mid-sized university in England. Biernat's shifting standards theory, which proposes that evaluative standards can shift due to stereotyping effects, was used to interpret the findings. Chi-square tests revealed significant effects of gender on the distribution and thematic content of nominations. Results suggested that students were more likely to nominate teachers of the same gender, but also that male students were disproportionately less likely to nominate a female teacher. Student conceptions of TE generally conformed to gender biases, particularly for male students. These findings indicate that students' perceptions of high quality teaching are inextricable from sociocultural influence. Future research can continue to engage with the shifting standards theory to investigate the influence of gender and student perceptions of high quality teaching.